Conceptualizing An Abundance Mentality and Its Relationship to Lifelong Learning, Human Flourishing, and Profound Learning - Ali Threet; Michael Kroth; Davin J. Carr-Chellman (Adult Education Research Conference, 2022)
The purpose of this exploratory literature review is to describe and continue to develop the concept of an abundance mentality and how it relates to lifelong learning, human flourishing, and profound learning.
Keywords: abundance mentality; human flourishing; profound learning